Customs Control of Goods: Balancing Protection and Facilitation in International Trade: An Analytical Study of Jordanian Customs Law - Al-Aroud, Oday Mahmoud (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: The study aims to address the concept and nature of customs control. customs bear the responsibility of reconciling customs facilities to encourage investments and increase competitiveness on one hand, and the inevitability of control on the other hand. Additionally, it discusses the impact of customs control on international trade, especially in light of the complete liberalization of foreign trade and Jordan’s accession to the World Trade Organization. Methods: In preparing this study, we relied on the descriptive analytical approach, analyzing a group of local legislative texts related to customs procedures. Results: The supervisory role played by the Customs Department is not limited to combating crimes affecting the state’s economy. It aims to achieve a balance between customs facilities and the necessity of oversight that ensures the collection of customs duties and the control of various customs crimes. While appreciating the various provisions regulating the conduct of customs control, it is necessary to issue new regulatory texts consistent with customs administrative regulation and global trade movements. Conclusions: Customs control does not serve a single purpose but rather multiple purposes simultaneously, achieving several goals. This is a usual reality given the intertwining of the state’s interests and the connections between them.